P697 Feasibility of HPV self-collection for cervix screening in under-screened street entrenched women. (14th July 2019) - Mitchell-Foster, Sheona; Racey, C.Sarai; Day, Tracey; Falkner, Celena; Smith, Laurie; Pedersen, Heather; Chan, Tracy; Cook, Darrel; Shannon, Kate; Lee, Marette; Money, Deborah; Allison, Sandra; et al.
Abstract : Background: HPV self-collection is a promising approach to improve uptake of cervical screening in under-screened women. The aim of this feasibility study was to measure uptake of HPV self-collection, HPV positivity, and screening history of street entrenched women in a rural region centre. Methods: Women 30–69 years of age, attending drop-in community-based primary care and integrative reproductive health clinics in Northern British Columbia (BC), Canada and self-reported not having received cervix screening in the last 3 years, were offered self-collection for HPV testing. A convenience sample of all comers was administered a questionnaire and underwent a medical chart review, including the provincial cervix screening registry. Demographics, HIV status, and cervix screening history were collected. All women who tested HPV16/18 positive were referred for colposcopy. Results: A total of 66 eligible women were analyzed (mean age 43.3 years), with population saturation reached after 3 months recruitment. An additional 11 women were deemed ineligible due to age or prior hysterectomy. 83% self-reported as Indigenous. Based on the provincial cervix screening registry, 48% of women were up-to-date on cervix screening based on triennial screening guidelines. All women undertook self-collection and the majority of women reported high perceived acceptability, safety, and accuracy of HPV self-collection. HPV 16/18 positivity was 7.6%, with 40% co-infected with HIV. Overall HIV prevalence was 16.4%, however, over 25% of women had unknown HIV status based on medical chart review. Conclusion: HPV self-collection was highly acceptable as part of community-based integrative reproductive health services. Despite being a traditionally underserved population, and women self-reporting being overdue for screening, over half the women were up to date on cervix screening, albeit regular screening was lacking for many. The findings from this feasibility study will inform future implementation of HPV self-collection to improve and maintain regular cervix screening services in street entrenched women. Disclosure: No significant relationships.